Direct numerical simulations on the flow past an inclined circular disk. (July 2017) - Tian, Xinliang; Hu, Zhihuan; Lu, Haining; Yang, Jianmin
Abstract: The three-dimensional flow past an inclined circular disk is investigated using direct numerical simulations. Various incidence angles of the disk with respect to the inflow are considered from 0 ° to 60 °, where 0 ° refers to the condition in which the flow is perpendicular to the disk. The aspect ratio (diameter/thickness) of the disk is considered to be 50. The Reynolds number based on the inflow velocity and the diameter of the disk is up to 500. The drag and lift coefficients, pressure coefficients, and three-dimensional vortical structures are analyzed using time-dependent and time-averaged techniques. Detailed comparisons between the results of the disk at different incidence angles are presented. The flow pattern gradually changes from chaotic to a periodic state as the incidence angle increases from 0 ° to 60 ° . At incidence angles of 45 ° and 50 °, an evident low-frequency modulation exists whose period is approximately ten times greater than the primary vortex shedding period. For the inclined disks, the wake flow is tilted to the trailing edge side of the disk rather than parallel to the streamwise direction. The distance between two successive vortical rings is observed to decrease as the incidence angle increases. The streamwise length of the mean recirculation bubble decreases as the incidence angle increases. Highlights: Flow around an inclined circular disk from 0 ° to 60 ° studied using DNS. The flow gradually changes from chaotic to the regular state as the inclined angle increases. The transition from periodic state to non-periodic state is delayed by the increased incidence angle. A low-frequency modulation is observed at the inclined angles of 45 ° and 50 ° .